THE ROLES OF NINIK MAMAK ON THE VICTORY OF MAHYELDI AND AUDY IN THE 2020 ELECTION IN AGAM REGENCY, WEST SUMATERA. - Khaira, Kintan Aghna; Wahid, Makmun; Rakhman, Moh. Arief; Maulana, Rio Yusri (JWP (Jurnal Wacana Politik), 2024)
This article analyzes the influence of ninik mamak (traditional leaders) on the victory of Governor Mahyeldi and Vice Governor Audy in the 2020 West Sumatra Governor Election in the Agam District. The influence of ninik mamak in shaping public perception can be observed in the political contestation during the West Sumatra gubernatorial election on December 9, 2020. The research aims to analyze how the influence of ninik mamak contributed to the success of the Mahyeldi and Audy pair and to identify the factors that enabled Mahyeldi and Audy to mobilize ninik mamak in the 2020 gubernatorial election in Agam, West Sumatra. This research utilizes a qualitative method with a descriptive approach. The results of this research indicate that ninik mamak socializes and communicates the vision and mission of Mahyeldi and Audy to the community through deliberation and consensus. Ninik mamak serves as a link between the interests of the candidates and the community or vice versa. They convince their descendants and influence the perception of voting for their descendants. The factors contributing to Mahyeldi and Audy’s ability to mobilize ninik mamak include identity factors. Mahyeldi, being a native of the Agam District, a Datuak within his community, a religious scholar or “buya” and representing intellectual elements based on his track record as the Mayor of Padang. Similarly, Audy, being an intellectual, played a role in this mobilization. Therefore, this became an asset for Mahyeldi to engage ninik mamak.